2020
DOI: 10.15252/embj.2020104749
|View full text |Cite
|
Sign up to set email alerts
|

CCR 5 deficiency impairs CD 4 + T‐cell memory responses and antigenic sensitivity through increased ceramide synthesis

Abstract: CCR5 is not only a coreceptor for HIV‐1 infection in CD4+ T cells, but also contributes to their functional fitness. Here, we show that by limiting transcription of specific ceramide synthases, CCR5 signaling reduces ceramide levels and thereby increases T‐cell antigen receptor (TCR) nanoclustering in antigen‐experienced mouse and human CD4+ T cells. This activity is CCR5‐specific and independent of CCR5 co‐stimulatory activity. CCR5‐deficient mice showed reduced production of high‐affinity class‐switched anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 75 publications
(103 reference statements)
4
20
0
Order By: Relevance
“…Considering recent reports showing that plasma lipid composition and order can alter the functional phenotype of T cells including Th cell subsets, membrane changes by ablation of very-long-acyl chain SLs might affect TCR signaling [ 47 ]. Formation of TCR oligomers at the cell surface is termed TCR nanoclusters, and recent study showed the inhibitory role of membrane ceramide in TCR nanoclustering [ 48 ]. In addition, increased CerS2 expression was correlated with the impaired TCR nanoclustering, and CerS2 silencing restored TCR nanoclustering and activation in OT-II CCR5 knockout CD4+ T cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering recent reports showing that plasma lipid composition and order can alter the functional phenotype of T cells including Th cell subsets, membrane changes by ablation of very-long-acyl chain SLs might affect TCR signaling [ 47 ]. Formation of TCR oligomers at the cell surface is termed TCR nanoclusters, and recent study showed the inhibitory role of membrane ceramide in TCR nanoclustering [ 48 ]. In addition, increased CerS2 expression was correlated with the impaired TCR nanoclustering, and CerS2 silencing restored TCR nanoclustering and activation in OT-II CCR5 knockout CD4+ T cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using complementary techniques, several studies have suggested that on the surface of a resting T cell, the TCR exists in a monomeric and in a nanoclustered form (Schamel et al, 2005 ; Lillemeier et al, 2010 ; Kumar et al, 2011 ; Sherman et al, 2011 ; Schamel and Alarcon, 2013 ; Pageon et al, 2016 ; Martín-Leal et al, 2020 ). Other studies only found low amount of TCR nanoclusters and thus concluded that nanoclusters would not exist (James et al, 2011 ; Rossboth et al, 2018 ).…”
Section: Cholesterol Regulates αβ Tcr Nanoclusteringmentioning
confidence: 99%
“…Likewise, the lipid ceramide reduced TCR nanoclustering (Martín-Leal et al, 2020 ). This was observed in liposomes as well as in T cells that were treated with sphingomyelinase, which hydrolyses sphingomyelin to ceramide.…”
Section: Cholesterol Regulates αβ Tcr Nanoclusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramide is an important component of the T cell receptor (TCR) signaling mechanism and pharmacological or molecular inhibition of ceramide production can impact on TCR-induced interleukin-2 production and disrupt programmed cell death (22). A recent study showed that increased synthesis of ceramide results in deficiency of C-C motif chemokine receptor 5 and weakens CD4 + T cell memory response and antigen sensitivity (23). However, the anti-tumor immune mechanism of ceramide in LUAD remains unknown.…”
Section: Introductionmentioning
confidence: 99%